Spectral quality of the shading and spacing on alpinia cultivation - de Souza, Roseane Rodrigues; Nascimento, Ângela Maria Pereira; Paiva, Patrícia Duarte de Oliveira; Almeida, Elka Fabiana Aparecida; Landgraft, Paulo Roberto Correa (Ornamental Horticulture, 2016)
Intensity and spectral quality of the radiation can be manipulated with the use of neutral or color shading screens in growing plants, and it can promote physiological and morphological changes. Therefore, the purpose was evaluating the effects of different shading levels, screens spectral quality, and spacing in the development of cv. Jungle King and cv. Jungle Queen gingers. Rhizomes were planted in 5 cultivation environments (full sun, black screen 50%, black screen 30%, blue screen 50% and red screen 50% shading) and 2 spacing (0.8 x 1.0 m and 0.8 x 1.5 m). The experimental design was completely randomized in a factorial 5x2x2x7, with 5 environments of cultivation, 2 cultivars, 2 spacing between plants and 7 times of evaluation (55, 120, 200, 255, 285, 335 e 370 days after planting (DAP)). The evaluations were shooting index, number of shoots per plant, shoot height and number of leaves per shoot. Shooting of cv. Jungle Queen was earlier compared to cv. Jungle King. Spacing did not influence in the initial development of plants. Screens with 50% shading, in blue or red colors, enhanced alpinia development.